Peningkatan Kemampuan Koneksi Matematis dan Self- Efficacy Siswa melalui Model Pembelajaran Kooperatif Tipe Rotating Trio Exchange (RTE) - Erna Isfayani; Rahmah Johar; Said Munzir (Universitas Hamzanwadi, 2018)
This study aims to determine the improvement of mathematical connection capability and self efficacy of students who have learned by Cooperative Learning Model Type Rotating Trio Exchange (RTE) compared to students who received conventional mathematics learning. Collection technique is done by doing test result of student learning and self-efficacy questionnaire of student. Data analysis of mathematical connection capability and student self-efficacy data were performed by using Independent-Sample t Test. The result of hypothesis testing shows that: (1) Improvement of mathematical connection ability of students who gain learning with RTE learning model better than mathematical connection ability of students who gain conventional learning; (2) Increased ability of self-efficacy of students who gain learning with RTE learning model better than the ability of self-efficacy of students who obtain conventional learning. Based on self-efficacy questionnaire indicated that students showed positive attitude toward mathematics learning using RTE Type Co-operative Model